Model Problem Based Learning Berbantuan Youtube Dalam Meningkatkan Motivasi Dan Hasil Belajar Siswa Pada Mata Pelajaran Geografi Di SMA - Nola Ifanisari, Riavi; Sriartha, Putu; Indra Christiawan, Putu (Universitas Muhammadiyah Surakarta, 2025)
The purpose of this study is to analyze: (1) the implementation of the Problem-Based Learning(PBL) model assisted by YouTube in geography learning, and (2) its effect on students’ learningmotivation and learning outcomes. This research was conducted at SMA Negeri 1 Penebel usinga quasi-experimental approach with a Non-Equivalent Control Group Design. Class samples wereselected through simple random sampling from equivalent class pairs, resulting in class X2 as theexperimental group (E) and class X4 as the control group (C). Data collection was carried out throughobservation, surveys, tests, documentation, and document analysis. The data were analyzed usingqualitative descriptive methods and inferential statistical analysis with a t-test. The results indicatethat: (1) the YouTube-assisted PBL model can be implemented by geography teachers with a very highlevel of effectiveness (score of 87.5), (2) the implementation of the model has a highly significanteffect on students’ learning motivation (significance value 0.000 < 0.05), and (3) on students’ academicachievement (significance value 0.003 < 0.05). Based on these findings, the YouTube-assisted PBLmodel is recommended as an interactive learning alternative for high school geography teachers toenhance student motivation and academic performance.